1999
DOI: 10.1074/jbc.274.33.23198
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Protozoan Uncoupling Protein in Acanthamoeba castellanii

Abstract: An uncoupling protein (UCP) has been identified in mitochondria from؉ cycling, early during phylogenesis before the major radiation of phenotypic diversity in eukaryotes and could occur in the whole eukaryotic world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 31 publications
2
80
0
Order By: Relevance
“…In the mitochondria of this amoeboid protozoon, the action of AcUCP has been shown to mediate the free fatty acid (FFA)-activated, PN-inhibited H + leak that can divert energy from oxidative phosphorylation during phosphorylating respiration (Jarmuszkiewicz et al 1999. It has also been shown that the treatment of amoeba cell cultures with cold temperatures increases the activity and protein levels of AcUCP, indicating that UCP could be a cold-response protein in unicellular eukaryotes (Jarmuszkiewicz et al 2004a).…”
Section: Introductionmentioning
confidence: 95%
“…In the mitochondria of this amoeboid protozoon, the action of AcUCP has been shown to mediate the free fatty acid (FFA)-activated, PN-inhibited H + leak that can divert energy from oxidative phosphorylation during phosphorylating respiration (Jarmuszkiewicz et al 1999. It has also been shown that the treatment of amoeba cell cultures with cold temperatures increases the activity and protein levels of AcUCP, indicating that UCP could be a cold-response protein in unicellular eukaryotes (Jarmuszkiewicz et al 2004a).…”
Section: Introductionmentioning
confidence: 95%
“…cDNAs of a UCP homologue present in Arabidopsis thaliana were also cloned and referred to as AtUCP cDNA [61]. Interestingly, using antibodies against plant UCP, Jarmuszkiewicz et al [62] detected a mitochondrial protein in the non-photosynthetic soil amoeboid protozoan Acanthamoeba catellanii.…”
Section: Figure 1 Northern Analysis Of Ucp1 Ucp2 and Ucp3 Mrnas In Mmentioning
confidence: 99%
“…The characterization of an uncoupling mechanism in a protozoan strongly suggests that the UCPs emerged, as specialized proteins for proton transport, early during phylogenesis and occur in the whole eukaryotic world [62]. Figure 5 shows that the three animal UCPs and the plant UCPs have the same root.…”
Section: Evolutionary Aspectsmentioning
confidence: 99%
“…Because the action of AcUCP is driven by the membrane potential, which depends on the cytochrome pathway activity (Jarmuszkiewicz et al 1999), it is not surprising that a significant decline either in the AcUCP activity and protein level was observed in mitochondria isolated from late H 2 O 2 -treated cells. Moreover, an increase in the amount of membranous Q and consequently a decrease in the Q reduction level (at a given influx of reducing substrates to the mitochondria) observed in the mitochondria from late H 2 O 2 -treated cells indicate that there is a low engagement of the present AcUCP.…”
Section: Discussionmentioning
confidence: 99%
“…The depletion of endogenous free fatty acids in the mitochondrial preparations was ensured by the presence of 0.4% fatty acidfree bovine serum albumin (BSA) in the isolation media except for the last mitochondrial washing (Jarmuszkiewicz et al 1999). The mitochondrial protein concentration was determined using the biuret method using BSA as a standard.…”
Section: Cell Culture and Mitochondrial Isolationmentioning
confidence: 99%